A new species of Indo-Pacific fish, Canthigaster criobe, with comments on other Canthigaster (Tetraodontiformes: Tetraodontidae) at the Gambier Archipelago - Williams, Jeffrey T.; Delrieu-Trottin, Erwan; Planes, Serge (Zootaxa, 2012)
A new species of the tetraodontid fish genus Canthigaster was discovered during a recent expedition to theGambier Archipelago, French Polynesia. The new species, named Canthigaster criobe herein, is the only knownspecies of Canthigaster having 12–14 brown stripes along the body (stripes beginning in front of the eye,extending along the body, and abruptly ending at the base of the caudal fin). It also has 17 pectoral rays, the originof the anal fin inserts posterior to a vertical from the rear base of the dorsal fin and lacks spots on the caudal fin.Canthigaster criobe is currently known from a single specimen collected at the Gambier Archipelago. It appearsto be most similar to the white-spotted C. janthinoptera, a wide-ranging, Indo-Pacific species, which also inhabitsthe Gambier Archipelago, and to the Hawaiian endemic C. jactator forming a species complex that exhibitsincomplete lineage sorting. Specimens of C. axiologus, or an undescribed but very similar sibling species, werealso collected at the Gambier Archipelago. Molecular analysis of these samples reveals an affiliation with C.axiologus specimens collected from disjunct localities in the western Central Pacific. Canthigaster axiologus wasnot previously known to occur east of the Tonga Islands. Geographic range expansions are also reported for C. rapaensis and C. amboinensis.